Case reportLate coarctation of aorta caused by protrusion of Amplatzer duct occluder – a case report of trans-catheter treatment - Dryżek, Paweł; Michalak, Krzysztof W.; Moszura, Tomasz; Moll, Jadwiga A.; Sysa, Andrzej (Advances in Interventional Cardiology/Postępy w Kardiologii Interwencyjnej, 2010)
A case of 9-year-old girl with Down syndrome and pulmonary hypertension, who has coarctation of aorta caused by protruded part of Amplatzer duct occluder implanted 3 years earlier. We described successful method of interventional treatment, with reset of patent ductus arteriosus (PDA) occluder device to gain good local conditions for CP stent implantation into aortal stenosis place. After procedure, there was no pressure gradient in descending aorta, CP stent was in proper position and the duct occluder was in position forced by pulling it back via femoral vein approach.